The role of multimodal imaging and vision function testing in ABCA4-related retinopathies and their relevance to future therapeutic interventions - Al-Khuzaei, S; Shah, M; Foster, CR; Yu, J; Broadgate, S; Halford, S; Downes, SM (SAGE Publications, 2021)
The aim of this review article is to describe the specific features of Stargardt disease and ABCA4 retinopathies (ABCA4R) using multimodal imaging and functional testing and to highlight their relevance to potential therapeutic interventions. Standardised measures of tissue loss, tissue function and rate of change over time using formal structured deep phenotyping in Stargardt disease and ABCA4R are key in diagnosis, and prognosis as well as when selecting cohorts for therapeutic intervention. In addition, a meticulous documentation of natural history will be invaluable in the future to compare treated with untreated retinas. Despite the familiarity with the term Stargardt disease, this eponymous classification alone is unhelpful when evaluating ABCA4R, as the ABCA4 gene is associated with a number of phenotypes, and a range of severity. Multimodal imaging, psychophysical and electrophysiologic measurements are necessary in diagnosing and characterising these differing retinopathies. A wide range of retinal dystrophy phenotypes are seen in association with ABCA4 mutations. In this article, these will be referred to as ABCA4R. These different phenotypes and the existence of phenocopies present a significant challenge to the clinician. Careful phenotypic characterisation coupled with the genotype enables the clinician to provide an accurate diagnosis, associated inheritance pattern and information regarding prognosis and management. This is particularly relevant now for recruiting to therapeutic trials, and in the future when therapies become available. The importance of accurate genotype-phenotype correlation studies cannot be overemphasised. This approach together with segregation studies can be vital in the identification of causal mutations when variants in more than one gene are being considered as possible. In this article, we give an overview of the current imaging, psychophysical and electrophysiological investigations, as well as current therapeutic research trials for retinopathies associated with the ABCA4 gene.